Feedback–feedforward control technique with a comprehensive mathematical analysis for single-input dual-output three-level dc–dc converter - Ganjavi, Amir; Gholinejad, Hamid Reza; Mehrasa, Majid; Ghoreishy, Hoda; Ahmad, Ahmad Ale (IET power electronics, 2020)
This study proposes a control technique for single-input dual-output three-level dc–dc converter (SIDO-TLC) using feedback (FB) and feedforward (FF) principles. Through the proposed control strategy, SIDO-TLC can smoothly function in both buck and boost operating conditions with a fast dynamic. Major duties of the designed FB control loops are to noticeably decrease the recovery time of transient responses under the load variations and accurately balance the boost capacitors voltages. To effectively decouple the introduced control inputs, an external FF controller is assigned that can also enhance the buck and boost voltage regulations. Furthermore, a step-by-step assessment is contemplated based on the proposed control loops to make an offline adjustment for the FB and FF coefficients. The proposed controller implemented on SIDO-TLC is highly suitable for portable applications, where efficiency, cost, and speed are of important factors. The simulation results and the laboratory test setup of SIDO-TLC using DSP TMS320F28335 are presented to prove the validity of the presented theoretical subjects.